دور المجتمع المدني في تنمية التحول الديمقراطي في بلدان المغرب العربي - مفتاح, عبد الجليل (revue mofakir; No 05 (2010): مجلـــة المفكــر, 2018)
دور المجتمع المدني في تنمية التحول الديمقراطي في بلدان المغرب العربي